1998
DOI: 10.1074/jbc.273.51.33905
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in Adenine Nucleotides Measured in Glucose-stimulated Rodent Islets Occur in β Cells but Not in α Cells and Are Also Observed in Human Islets

Abstract: Glucose metabolism by pancreatic ␤ and ␣ cells is essential for stimulation of insulin secretion and inhibition of glucagon secretion. Studies using rodent islets have suggested that the ATP/ADP ratio serves as second messenger in ␤ cells. This study compared the effects of glucose on glucose oxidation ([U-14 C]glucose) and adenine nucleotides (luminometric method) in purified rat ␣ and ␤ cells. The rate of glucose oxidation at 1 mM glucose was higher in ␤ than ␣ cells (4.5-fold, i.e. ϳ2-fold after normalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
131
2
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 43 publications
18
131
2
1
Order By: Relevance
“…Actually, in concurrence with the conclusion that insulin secretion might be controlled by the cytosolic ATP/ADP ratio (22), there is evidence in favor of both sites. First, in resting pancreatic ␤-cells, estimates of the cytosolic concentration of ATP range from 0.6 to 3 mmol/l (19,(22)(23)(24) and those of ADP, from 0.3 to 1.2 mmol/l (19,22). Consistent with previous reports (25), our experiments show modulation of channel activity if at 300 mol/l GDP the ATP concentration varies ϳ1 mmol/l (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Actually, in concurrence with the conclusion that insulin secretion might be controlled by the cytosolic ATP/ADP ratio (22), there is evidence in favor of both sites. First, in resting pancreatic ␤-cells, estimates of the cytosolic concentration of ATP range from 0.6 to 3 mmol/l (19,(22)(23)(24) and those of ADP, from 0.3 to 1.2 mmol/l (19,22). Consistent with previous reports (25), our experiments show modulation of channel activity if at 300 mol/l GDP the ATP concentration varies ϳ1 mmol/l (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Notably, the mitochondrial substrate pyruvate was more efficient than glucose in provoking glucagon secretion from the αTC1-6 cells; this coincided with a minor, albeit significant, increase in the OCR also observed in the αTC1-6 cells. These results confirm findings from primary islet cells in which glucose-provoked ATP [22,47] and FADH 2 production [48] have been shown to be lower in the α-cell than in the β-cell. Overall, our findings of less efficient coupling of glycolysis and TCA-cycle metabolism in the αTC1-6 cell line support other studies in which mitochondrial metabolism has been shown to be significantly more glucose-responsive in the β-cell [22,23,49].…”
Section: Figure 8 Gsis From Mouse Islets Is Unaffected By Phs Whereasupporting
confidence: 90%
“…3B). Because [ATP] i is unlikely to fall below 0.1 mM in beta cells, even when extracellular glucose is low (12), the difference in wild-type and mutant K ATP current at this (and higher) ATP concentration probably explains why the R201C and R201H mutations result in neonatal diabetes. Accumulating evidence implicates small changes in K ATP current with impaired insulin secretion (11).…”
Section: Resultsmentioning
confidence: 99%